Developing a Decision Aid Tool for selecting pen-paper observational ergonomics techniques: a quasi-experimental study - Tajvar, Abdolhamid; Daneshmandi, Hadi; Seif, Mozhgan; Parsaei, Hossein; Choobineh, Alireza (La Medicina del Lavoro, 2022)
Background: A significant error that may occur during ergonomic risk assessment and invalidate assessment reliability corresponds to technique selection. This study aimed to develop a new tool called the Decision Aid Tool (DAT) to reduce pen-paper observational technique selection errors. Methods: This quasi-experiment before-after study was performed in three phases. In the first phase, the participants’ skills in technique selection were examined by showing them 20 videos of different single-task jobs. In the second phase, the DAT was designed using pen-paper observational techniques. Finally, in the third phase, 115 occupational health specialists included in the study through purposive sampling of experts evaluated the tool’s efficacy. Results: The results of the first phase showed that 62% of participants made an error in selecting the proper technique. The mean and standard deviation scores from the first and third phases were 11.4 ± 6.59 and 39.01 ±1.89, respectively. The mean scores increased significantly after using DAT, and 97.5% of participants could correctly select task techniques. Conclusions: The efficacy of DAT was confirmed in a quasi-experimental before-and-after study. Using DAT increases the participants’ ability to choose the correct technique. The DAT can be functional for practitioners to select the pen-paper observational techniques correctly under the purpose of assessment, the body areas, and the characteristics of the task to be assessed.